COVID-19 Incidence and Mortality Among Unvaccinated and Vaccinated Persons Aged ≥12 Years by Receipt of Bivalent Booster Doses and Time Since Vaccination — 24 U.S. Jurisdictions, October 3, 2021–December 24, 2022 - Johnson, Amelia G.; Linde, Lauren; Ali, Akilah R.; DeSantis, Allison; Shi, Minchan; Adam, Carolyn; Armstrong, Brandy; Armstrong, Brett; Asbell, Madison; Auche, Steven; Bayoumi, Nagla S.; Bingay, Boudu; et al. (MMWR. Morbidity and mortality weekly report, 2023)
On September 1, 2022, CDC recommended an updated (bivalent) COVID-19 vaccine booster to help restore waning protection conferred by previous vaccination and broaden protection against emerging variants for persons aged ≥12 years (subsequently extended to persons aged ≥6 months).* To assess the impact of original (monovalent) COVID-19 vaccines and bivalent boosters, case and mortality rate ratios (RRs) were estimated comparing unvaccinated and vaccinated persons aged ≥12 years by overall receipt of and by time since booster vaccination (monovalent or bivalent) during Delta variant and Omicron sublineage (BA.1, BA.2, early BA.4/BA.5, and late BA.4/BA.5) predominance. During the late BA.4/BA.5 period, unvaccinated persons had higher COVID-19 mortality and infection rates than persons receiving bivalent doses (mortality RR = 14.1 and infection RR = 2.8) and to a lesser extent persons vaccinated with only monovalent doses (mortality RR = 5.4 and infection RR = 2.5). Among older adults, mortality rates among unvaccinated persons were significantly higher than among those who had received a bivalent booster (65-79 years; RR = 23.7 and ≥80 years; 10.3) or a monovalent booster (65-79 years; 8.3 and ≥80 years; 4.2). In a second analysis stratified by time since booster vaccination, there was a progressive decline from the Delta period (RR = 50.7) to the early BA.4/BA.5 period (7.4) in relative COVID-19 mortality rates among unvaccinated persons compared with persons receiving who had received a monovalent booster within 2 weeks-2 months. During the early BA.4/BA.5 period, declines in relative mortality rates were observed at 6-8 (RR = 4.6), 9-11 (4.5), and ≥12 (2.5) months after receiving a monovalent booster. In contrast, bivalent boosters received during the preceding 2 weeks-2 months improved protection against death (RR = 15.2) during the late BA.4/BA.5 period. In both analyses, when compared with unvaccinated persons, persons who had received bivalent boosters were provided additional protection against death over monovalent doses or monovalent boosters. Restored protection was highest in older adults. All persons should stay up to date with COVID-19 vaccination, including receipt of a bivalent booster by eligible persons, to reduce the risk for severe COVID-19.